Relentless [compact disc, unabridged] : a novel - Koontz, Dean R. (Dean Ray), 1945- (Brilliance Audio, 2009)
Cubby, an author, receives triumphant reviews across the board for his book, except from the much-feared, seldom-seen critic Shearman Waxx, who makes vicious, inaccurate remarks in the nation's premier newspaper. Cubby only wants to get a look at the mysterious recluse whose mere opinion can make or break a career or a life. Shearman Waxx isn't what Cubby expects and neither is the escalating terror that follows what seemed to be an innocent encounter.